Screen-Printed Carbon Electrode Modified with Poly-L-histidine Applied to Gold(III) Determination - Bergamini, Marcio F. [UNESP]; Santos, Daniela P. [UNESP]; Zanoni, Maria Valnice Boldrin [UNESP] (Soc Brasileira Quimica, 2009)
O presente trabalho reporta o desenvolvimento de um novo método voltamétrico para análise de íons ouro(III) usando eletrodo de carbono impresso modificado com poli-L-histidina. O procedimento é baseado no acúmulo do complexo [AuCl4]-, na superfície do eletrodo sob potencial de circuito aberto e tempo de acúmulo controlado. Parâmetros que influenciam na resposta, tais como: preparação do filme, pH, potencial de acúmulo e tempo de acúmulo, foram otimizados e curvas analíticas para os íons ouro foram construídas usando voltametria de varredura linear (LSV), pulso diferencial (DPV), e onda quadrada (SWV). Limites de detecção de 6,0 × 10-6 mol L-1, 1,7 × 10-6 mol L-1 e 4,0 × 10-6 mol L-1 foram obtidos para LSV, DPV e SWV, respectivamente. O método foi aplicado para a determinação de íons ouro em amostras de urina humana.

A sensitive voltammetric method for trace measurements of gold(III) ions using a screen-printed carbon electrode modified with poly-L-histidine is described. The new procedure is based on the accumulation of the tetrachloroaurates complex at the electrode surface under an open circuit potential condition, followed by a cathodic stripping scan of potential. Parameters such as film preparation, pH, accumulation potential and deposition time have been optimized to obtain the best voltammetric response. Using optimal experimental conditions, analytical curves for gold ions were obtained using a linear sweep (LSV), differential pulse (DPV), and square wave voltammetry (SWV). Limits of detection of 6.0 x 10(-6) mol L(-1), 1.7 x 10(-6) mol L(-1) and 4.0 x 10(-6) mol L(-1) were estimated for the LSV, DPV and SWV, respectively. The method was successfully applied to the determination of gold ions in human urine samples.
Keywords: screen-printed electrode; poly-L-histidine; gold ions; stripping voltammetry